Land Degradation and Restoration Driven by Invasive Alien -Prosopis Juliflora and the Banni Grassland Socio-Ecosystem (Gujarat, India) (Global Journal of Science Frontier Research, 2021)
Land Degradation and alien species invasions gained significant attention of the scientific community and the intergovernmental establishment. This review presents a case in which these two processes jointly interact with an ecosystem -the Banni grassland -and its users over six decades. Banni is an arid, yet productive rangeland that supports a pastoral community raising grass-cover-dependent livestock. A bush/tree alien species, Prosopis juliflora, initiated a land degradation process by outcompeting the grass-cover species, thus undermining the pastoral livelihood. Rather than yield to the prevailing approach of eradicating an invasive species, the community and authorities considered cultural, scientific, and policy issues, and worked together to initiate linked processes of the invasive species naturalization and the grassland ecosystem transformation, to a mosaic of grassland and bush/tree woodland patches ecosystem.
Keywords: banni; kachchh; charcoal; prosopis juliflora; land degradation; ecosystem services; alien invasive species